2010
DOI: 10.1080/13683500802684411
|View full text |Cite
|
Sign up to set email alerts
|

Inbound tourism and long-run economic growth

Abstract: There is an upsurge of literature investigating the relationship between inbound tourism expansion and economic growth with special emphasis on developing countries. Some countries -such as Spain and Italy -can be taken as examples of demonstrating such a successful trajectory. This paper provides an empirical investigation of the evolution of the Spanish and Italian economies and their respective tourism sectors from the 1950s and 1960s, respectively. This research is theoretically based on the literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(84 citation statements)
references
References 42 publications
2
72
0
Order By: Relevance
“…Since then, the first paper that formally confirmed the tourism-led growth hypothesis through cointegration and causality tests for the case of the Spanish economy was published in 2002 (Balaguer & Cantavella-Jordá, 2002). Several other time series studies showing the relationship between tourism and economic growth reported a long run equilibrium relationship and evidence for causality among the variables of interest specifically for southern European Mediterranean countries (Cortés-Jiménez & Pulina, 2010;Dritsakis, 2004;Eeckels, Filis, & Leon, 2012;Gunduz & Hatemi-J, 2005;Katircioglu, 2007;Kim, Chen, & Jang, 2006;Massidda & Mattana, 2013;Nowak, Sahli, & Cortés-Jiménez, 2007).…”
Section: Brief Review Of Earlier Studiesmentioning
confidence: 89%
“…Since then, the first paper that formally confirmed the tourism-led growth hypothesis through cointegration and causality tests for the case of the Spanish economy was published in 2002 (Balaguer & Cantavella-Jordá, 2002). Several other time series studies showing the relationship between tourism and economic growth reported a long run equilibrium relationship and evidence for causality among the variables of interest specifically for southern European Mediterranean countries (Cortés-Jiménez & Pulina, 2010;Dritsakis, 2004;Eeckels, Filis, & Leon, 2012;Gunduz & Hatemi-J, 2005;Katircioglu, 2007;Kim, Chen, & Jang, 2006;Massidda & Mattana, 2013;Nowak, Sahli, & Cortés-Jiménez, 2007).…”
Section: Brief Review Of Earlier Studiesmentioning
confidence: 89%
“…Therefore, the study endorses the vindication of the tourism-led growth hypothesis. On the contrary, Nowak et al (2007) and Cortés-Jiménez and Pulina (2010) found evidence of bidirectional causality between tourism and economic growth in Spain. , , and Cortés-Jiménez and Pulina (2010) assessed the causal relationship between tourism and economic growth in Italy using the Johansen-Juselius cointegration and Granger causality tests.…”
Section: Insights From the Literaturementioning
confidence: 98%
“…Nevertheless, the indicators used to measure tourism often depend on data availability, especially when the scope of the study is regional or provincial. Thus, for example, in the studies by Cortés-Jiménez and Pulina [40] and Gómez-Calero et al [41], tourism is measured as the number of travelers staying overnight at hotels and additionally as the number of hotel overnight stays. However, overnight stays may be considered a better proxy of the earnings obtained from tourism [41].…”
Section: Datamentioning
confidence: 99%